Shift in Fiji's Cooperation and Foreign Policy from China to Australia during the period of 2022-2023 - Muhammad Ficky Yusuf (Dinasti International Journal of Education Management And Social Science, 2024)
Countries in the world frequently experience alterations in their collaboration and foreign policy. Fiji is a nation located in the South Pacific region that recently underwent alterations in its foreign political collaboration. The previously strong alliance between Fiji and China, which was formed during the coup in 2006, experienced a quick decline and transformation when Fiji decided to prioritize its relations with Australia. This transition occurred due to Australia's frequent disagreements with China on the global stage. The shift in Fiji's foreign policy from China to Australia over the era of 2022-2023 prompts the inquiry into the rationale behind this decision, given the contrasting positions of Australia and China in the global arena. This study employs the balance of threat theory, which involves countries in the international system striving to achieve a state of equilibrium in power with other nations, in order to minimize the risks and dangers they face. This study employs a qualitative methodology, including data collection methods such as literature reviews, scientific papers, and reputable news media sources. The study findings suggest that Fiji is engaging in a strategy of balancing against China because to the perceived higher level of threat posed by Australia. This research is anticipated to offer empirical investigations to assist countries in addressing analogous circumstances.